2017
DOI: 10.1111/ajt.14134
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Outcomes of Living Liver Donors From a Multicenter Prospective Study: Results From the Adult-to-Adult Living Donor Liver Transplantation Cohort Study2 (A2ALL-2)

Abstract: While single-center and cross-sectional studies have suggested modest impact of liver donation on donor psychological well-being, few studies have assessed these outcomes prospectively among a large cohort. We conducted one of the largest, prospective, multi-center studies of psychological outcomes in living liver donors within the Adult-to-Adult Living Donor Liver Transplantation Cohort Study (A2ALL-2) Consortium. 271 (91%) of 297 eligible donors were interviewed at least once at pre-donation, 3-, 6-, 12- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 41 publications
4
47
0
Order By: Relevance
“…The duration of hospital stay after donor operation was significantly longer and perioperative complications with Clavien classification greater than grade IIIa were more frequent in donors with psychiatric complications than in those without psychiatric complications. In LDLT donors, age and sex, relationship with recipient, ambivalence and motivation to be LDLT donor, feeling for donation, and hospitalization have all also been reported to be associated with psychiatric complications [8,25]. Our observations were consistent with previous reports that suggested that the development of postoperative psychiatric complications was associated with postoperative physical complications [5,6,26,27].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The duration of hospital stay after donor operation was significantly longer and perioperative complications with Clavien classification greater than grade IIIa were more frequent in donors with psychiatric complications than in those without psychiatric complications. In LDLT donors, age and sex, relationship with recipient, ambivalence and motivation to be LDLT donor, feeling for donation, and hospitalization have all also been reported to be associated with psychiatric complications [8,25]. Our observations were consistent with previous reports that suggested that the development of postoperative psychiatric complications was associated with postoperative physical complications [5,6,26,27].…”
Section: Discussionsupporting
confidence: 91%
“…Although LDLT donors with psychiatric complications have been previously reported [1,8,19], little is discussed about long-term outcomes of LDLT donors who required psychiatric treatment. Additionally, there are no reports regarding the effects and outcomes of psychiatric treatment delivered by psychiatrists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ours is one of the largest studies conducted on the psychological outcomes of living donors of low socioeconomic status in the United States. RELIVE, A2ALL, and several other studies indicate that living donors durably enjoy high life satisfaction 1,8,9,11,12,24,37 . This may be related to high self‐esteem, pride, and validation of well‐being through a generous act and external acknowledgment.…”
Section: Discussionmentioning
confidence: 90%
“…Those donors who do not have enough time to make a decision may show depression symptoms [23]. On the other hand the survival of the recipient play an active role on donor's unwillingness to donate again [24]. According to DuBay, et al [25] researchers should pay more attention to the donors who have been diagnosed with psychiatric disorders or who are young or have had further education.…”
Section: Resultsmentioning
confidence: 99%